The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/jgr-05-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability reporting-firm performance nexus: evidence from a threshold model

Abstract: Purpose This study aims to provide a convincing argument behind the mixed findings on the association between sustainability reporting and firm performance by investigating the possibility of a non-linear relationship through a threshold model. Design/methodology/approach This study used (Hansen’s 1999) threshold framework to investigate the relationship between firm performance and sustainability reporting using a sample of 210 Bombay Stock Exchange-listed firms spanning over 10 years from March 2010 to Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 89 publications
2
28
0
Order By: Relevance
“…Friede et al (2015) argued that the relationship between ESG performance and corporate financial performance dates back to the 1970s, and since then, more than 2,000 empirical studies have been published. Bansal et al (2021) identified three streams of research in this debate. Each stream argues that the correlation between ESG and financial performance is different – positive, negative or non-significant.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Friede et al (2015) argued that the relationship between ESG performance and corporate financial performance dates back to the 1970s, and since then, more than 2,000 empirical studies have been published. Bansal et al (2021) identified three streams of research in this debate. Each stream argues that the correlation between ESG and financial performance is different – positive, negative or non-significant.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Scholars in the first research stream (positive correlation) argue that acting in a socially and environmentally responsible manner is not significantly costly and that firms can benefit financially from their social and environmental responsibilities (McGuire et al , 1988). According to these studies, superior EGS performance positively affects stakeholders’ views of the company, increasing market value (Bansal et al , 2021). Departing from value-creation theory, they claimed that superior ESG performance can lead to a competitive advantage (Bansal et al , 2021).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations